Só mais um... entendendo a importância do binge watching em plataformas de video on demand - Costa, Laura Maria Aguiar (2019)
This study aimed to understand the importance of the practice of binge watching in behavioral intentions and in the use of Video On Demand platforms, based on the transformations observed in series consumption and content distribution technologies. The literature review reached through the analysis of studies on consumer culture, entertainment consumption, binge watching and works involving models for adoption of technologies, identification of determinants and their relation with the constructs of interest of the research, obtaining as a result 11 hypotheses to be tested. The methodological procedures involve the elaboration of a structured questionnaire, with items of scales validated and adapted to the context of this study. The collected data were analyzed based on an initial exploratory analysis, multivariate analysis techniques, processed in SPSS 22 and modeling of structural equations using SmartPLS 3 to verify the hypothesis of the research. As results we have that the relationships of the constructs performance expectation, social interaction, facilitative conditions, hedonic motivations, price value, habit and content are determinants of the behavioral intention construct, which significantly predicts the use of Video On Demand platforms by users of binge watching. Therefore, this study brings an adaptation of the UTAUT2 model to the application in the Brazilian context of the platforms of streaming before the modifications in the habits of series binge watching.